The Influence of Celebrity Influencers' Credibility and Online Customer Reviews on Purchase Intention: The Mediating Role of Consumer Attitudes - Angelia Laksana; Irantha Hendrika; Gladys Greselda Gosal (Jurnal Manajemen dan Ekonomi Kreatif, 2025)
This study aims to analyze the influence of celebrity influencers' credibility and online customer reviews on purchase intention, with consumer attitudes as a mediator. The research employs a quantitative approach, utilizing a questionnaire distributed via Google Forms to 160 Gen Z respondents in Surabaya. Results indicate that celebrity influencers' credibility significantly impacts consumer attitudes and purchase intention directly and indirectly through consumer attitudes. Similarly, online customer reviews have a significant impact on purchase intention directly and indirectly through consumer attitudes. The findings highlight the importance for businesses to strategically leverage credible influencers and encourage positive online reviews to enhance consumer attitudes and drive purchase intentions.